Konsep Iman dan Kufur Menurut Mu’tazilah Analisis Buku Teologi Islam Harun Nasution - Siregar, Uswatul Hasanah (Lembaga Yasin AlSys, 2023)
Faith is the principle and basis for all human deeds, believes in the heart, verbally pronounces the creed, and all the movements of his life are a manifestation of obedience to Allah and His Messenger. Kufr is denying Allah from all aspects, denying His existence, denying His oneness, denying His favors that are bestowed on humans, denying the truth and teachings brought by His messenger from Allah swt. Faith and disbelief are two contradictory things, in this study. Researchers want to examine more deeply about the concept of faith and disbelief according to muktazilah. The method used is library research, namely research that uses library literature, which grows on studies and texts. namely making library materials the main source of data Based on research conducted that faith and disbelief in Islamic theology the Mu'tazilah concept of faith is what they identify as knowledge with reason. As for the concept of kufr according to Mu'tazilah, kufr is aimed at people who are entitled to receive severe punishment in hell. Therefore, those who commit major sins are not disbelievers, they will not receive severe punishment in hell. However, because he is not a believer, he cannot be put into heaven. So his place is hell, on the basis of justice, he is put into hell with lighter punishment.